Efectividad de la punción seca en los músculos del manguito rotador para el tratamiento de hombro doloroso: revisión sistemática - Rodríguez Pillajo, Genis Lizeth (2020)
OBJECTIVE: To carry out a systematic review on the effectiveness of dry puncture in the rotator cuff muscles for the treatment of painful shoulder. MATERIAL AND METHOD: The search strategy was carried out using the main databases of published works including: Scopus, Web of Science, Pubmeb, Pro Quest, COCHRANE LIBRARY, PEDro and Google Scholar. The search strategy was for articles with an emphasis on the English language without time, age or gender limits using the following keywords: Rotator Cuff or Trigger Points or Dry Needling or Treatment or Shoulder Pain or Myofascial Pain Syndrome. These words were combined using the Boolean operators AND and OR in order to broaden the search and find the most relevant information in the present study. RESULTS: The functionality in relation to the age of the patients between 18 and 65 years of age was the closest to being significant, since in seven studies the patients indicated increased functionality after the application of both superficial and deep dry needling. But when performing the Chi-square2 and observing the data, they do not have a significant p 0.118. CONCLUSIONS: The lack of effectiveness in some diagnostic aspects makes the barriers to the adoption of clinical recommendations on dry needling based on weak or conflicting evidence, as demonstrated by the studies that have been approved for publication in databases. Important data, does not throw objective data towards a unified procedure that allows the improvement of the patient in terms of pain, mobility and functionality. KEY WORDS: Rotator Cuff or Trigger Points or Dry Needling or Treatment or Shoulder Pain or Myofascial Pain Syndrome.